CTNI-25. REGORAFENIB IN RECURRENT GLIOBLASTOMA PATIENTS: A MULTICENTRIC REAL-LIFE STUDY. (14th November 2022) - Bruno, Francesco; Pellerino, Alessia; Pronello, Edoardo; Palmiero, Rosa; Polo, Valentina; Vitaliani, Roberta; Trincia, Elena; Internò, Valeria; Porta, Camillo; Soffietti, Riccardo; Rudà, Roberta
Abstract: BACKGROUND: In the phase 2 REGOMA trial, regorafenib improved overall survival, as compared to lomustine, for glioblastoma (GBM) patients at first progression after chemoradiation. Here, we present the results of a real-life multicentre study that analysed response to treatments, tolerability, and outcome of GBM patients treated with regorafenib at first tumour progression. PATIENTS AND METHODS: Regorafenib was given following an escalation dose protocol (1 st cycle: 80 mg/day for 2 weeks, then 120 mg/day for one week; 2 nd cycle: 120 mg/day for 2 weeks, then 160 mg/day for one week; 160 mg/day from the 3 rd cycle). Progression-free survival (PFS) and overall survival (OS) were defined as time from regorafenib initiation and disease progression or death. RESULTS: From January 2020 to January 2022, 66 GBM patients were included. Median age was 60.0 years. MGMT p methylation was found in 30 patients (45.5%). Median dose was 120 mg/day 21q28 day, which was lower than that used in REGOMA trial (149 mg). Median PFS (mPFS) was 2.7 months and median OS (mOS) 7.1 months. RANO response to regorafenib was partial response (PR) in 10 (15.1%), stable disease in 14 (21.2%), and progressive disease in 42 (63.7%) patients. Forty-six (69.7%) patients presented adverse events of any grade, and 21 (31.8%) grade III-IV toxicity. Two patients only (3.0%) interrupted regorafenib due to toxicity. In a multivariable analysis, factors associated with disease progression were higher age (p = 0.035) and absence of MGMT p methylation (p = 0.024). CONCLUSION: In our study, mPFS and mOS were similar to those of the 59 patients enrolled in the regorafenib arm of REGOMA trial (2.7 vs 2.0 months; 7.1 vs 7.4 months, respectively). However, we observed a higher rate of PRs (15% versus 3.0%). Moreover, we had a lower incidence of discontinuations due to toxicity, maybe because of the lower dose intensity.